Towards a Hybrid Federated Cloud Platform to Efficiently Execute Bioinformatics Workflows - Saldanha, Hugo; Ribeiro, Edward; Borges, Carlos; Araújo, Aletéia; Gallon, Ricardo; Holanda, Maristela; Walter, Maria Emília; Togawa, Roberto; Setubal, João Carlos (IntechOpen, 2012)
None